Cumulative effect of microwave sterilization on the physical properties of microwave polymerized and conventional heat-polymerized acrylic resin - S Mohammed Shafeeq; S Karthikeyan; Subash M Reddy; Suma Karthigeyan; R Manikandan; Arthiie Thangavelu (Wolters Kluwer Medknow Publications, 2016)
Aims: To evaluate and compare the flexural strength and impact strength of conventional and microwave cured denture base resins before and after repeated sterilization using microwave energy to consider microwave curing as an alternative to the conventional method of sterilization. Materials and Methods: The conventional heat cure acrylic resin (DPI heat cure material) Group A and microwave-polymerized acrylic resin (Vipi Wave Acrylic resin) Group B were used to fabricate 100 acrylic resins samples using a standard metal die of (86 mm × 11 mm × 3 mm) dimensions. The criterion was flexural strength and impact strength testing which had Group A and Group B samples; 50 samples for flexural strength and 50 samples for impact strength measurement. For each criterion, five control samples were taken for Group A and Group B. The samples were stored in water before experimenting. The test samples were subject to four cycles of microwave sterilization; followed by flexural strength testing with a 3-point flexural test in universal testing machine (UNITEK 94100) and impact strength testing with impact testing machine (ENKAY Pr09/E1/16). Results: The physical properties had significant changes for conventionally cured denture base resins, whereas no changes found for microwave-cured resins after repeated sterilization cycles.